High Convertion Ratio Power Converterfor Electric Vehicle Application - JL, Juliha.; Joseph.J, Jency; F.T, Josh. (International Journal of Engineering and Technology, 2018)
In Electric Vehicle applications, the converters play a significant role by stepping up or stepping down the input voltage and feeds the motor. The implementation and the mathematical analysis of the DC-DC Converters are analysed and presented here. This paper gives the better view of Zeta converter, Superlift Luo converter and Cascaded boost converterruns the BLDC motor with constant voltage for the electric vehicle and the simulation is carried out by the MATLAB/SIMULINK. The simulation results of the proposed DC-DC converters are compared with the analysed values.Â Â